KREASI IKAT ENDEK SEBAGAI PRODUK PENUNJANG PARIWISATA BALI - I Gusti Ayu Melistyari Dewi; I Wayan Ardika; I Nyoman Sunarta (Magister Tourism Study, Faculty of Tourism, Udayana University, 2019)
As a tourism destination in the world, Bali attracts many tourists to visit because of its tourist attractions and culture. One form of Balinese cultural products is Balinese endek, a traditional Balinese fabric comes in a myriad of beautiful colors and geometrical designs. The experience of weaving Balinese Endek is the phenomenon of commodification in its essence as a creative industry. The author uses this paper to be able to critically examine the Balinese Endek function with a culture studies approach in relation to the use of endek in the tourism sector. The instrument for analyzing this paper is using the commodification theory, which is explaining about something that is not related to the production process into a product that is consumed in bulk, yet is related to how a product is marketed to the target market in order to meet consumer needs.The methodology used in examining the phenomenon of the commodification of Balinese endek is a critical method that is emancipatory in nature, namely the involvement of producers or weavers and business people (who are involved in the tourism industry). The results of this paper are: (1) The symbolic meaning that is typical of Balinese Endek is an attraction and has the potential to attract tourists, thus helping to improve the economy of the Balinese people. (2) The dynamics of Balinese Endek marketing in the market are in demand by the local market as well as the global market as a creative product. (3) The development of function of the Balinese endek not solely by the local community, but also by tourists to be used as a souvenir. Keywords: Commodification, Tenun Ikat Endek Bali, Bali Tourism